2015
DOI: 10.1152/ajpregu.00168.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin 177, prolactin 188, and extracellular osmolality independently regulate the gene expression of ion transport effectors in gill of Mozambique tilapia

Abstract: This study characterized the local effects of extracellular osmolality and prolactin (PRL) on branchial ionoregulatory function of a euryhaline teleost, Mozambique tilapia (Oreochromis mossambicus). First, gill filaments were dissected from freshwater (FW)-acclimated tilapia and incubated in four different osmolalities, 280, 330, 380, and 450 mosmol/kg H2O. The mRNA expression of Na(+)/K(+)-ATPase α1a (NKA α1a) and Na(+)/Cl(-) cotransporter (NCC) showed higher expression with decreasing media osmolalities, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 81 publications
5
39
0
Order By: Relevance
“…In tilapia, Ncc-expressing ionocytes (type II ionocytes) are key effectors of Cl − uptake , Horng et al 2009), and we have shown that Prl stimulates ncc expression and the recruitment of Ncc-expressing ionocytes in vivo (Breves et al 2010c). Employing the presence of Ncc-expressing ionocytes as readout of Prl responsiveness (Breves et al 2010c, Inokuchi et al 2015, we confirmed the utility of the filament incubation system to model physiological responses to Prl (Fig. 7).…”
Section: :3supporting
confidence: 70%
See 1 more Smart Citation
“…In tilapia, Ncc-expressing ionocytes (type II ionocytes) are key effectors of Cl − uptake , Horng et al 2009), and we have shown that Prl stimulates ncc expression and the recruitment of Ncc-expressing ionocytes in vivo (Breves et al 2010c). Employing the presence of Ncc-expressing ionocytes as readout of Prl responsiveness (Breves et al 2010c, Inokuchi et al 2015, we confirmed the utility of the filament incubation system to model physiological responses to Prl (Fig. 7).…”
Section: :3supporting
confidence: 70%
“…These modulations of gene expression occurred in response to plasma osmotic conditions routinely experienced during the acute phases of FW (~280 mOsm/kg) and SW (~450 mOsm/kg) acclimation (Inokuchi et al 2015). Hyperosmotic conditions stimulate the gene expression of Na + /K + /2Cl − cotransporter 1a (nkcc1a), a key cotransporter underlying ion extrusion by teleost ionocytes , Inokuchi et al 2015, as well as volume regulation by pavement cells (Tse et al 2007). Thus, enhanced aqp3/Aqp3 expression in the basolateral region of branchial cells in FW-acclimated tilapia (Fig.…”
Section: :3mentioning
confidence: 99%
“…For example, branchial ncc2 expression is highly labile in tilapia, with a marked increase in expression occurring within hours of transfer from SW to FW, and decreased expression following transfer from FW to SW (Hiroi et al 2008, Breves et al 2011). The dynamics of ncc2 align closely with the morphological and functional changes occurring within FW-type ionocyte populations during salinity acclimation (Hiroi et al 2008, Inokuchi et al 2008) and following hormone treatments (Breves et al 2010c, Inokuchi et al 2015, Watanabe et al 2016). ncc2 transcript levels thus provide a point of reference from which to characterize parallel transcriptional responses underlying FW acclimation.…”
Section: Introductionsupporting
confidence: 63%
“…Inasmuch as the acute phase of salinity acclimation entails deviations from internal ‘set-points’ before effector mechanisms are fully activated, these deviations themselves may initiate changes in gill function (Marshall et al 2000, Tse et al 2007, Inokuchi et al 2015). In this regard, cells comprising branchial epithelia operate as osmoreceptors in addition to responding to systemic hormones (Zadunaisky et al 1995, Hiroi et al 2005, Marshall et al 2008, Kültz 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation